Perspektif Masyarakat terhadap Pencemaran Udara di Kawasan TPA Terjun Kota Medan - Putri Erma Yunita; Aldian Setia Luhur; Nurhalizah Pasha; Hamidatus Salihah; Sari Wulandari (Pusat Riset dan Inovasi Nasional, 2025)
Waste is a problem that needs attention because it can have a negative impact on the environment and human health. Medan City, including North Sumatra, has a waste management problem that has not been optimized. One of the landfills in Medan City is Terjun Landfill. Air pollution in the Terjun landfill area of Medan City is a serious problem that affects the quality of life of the surrounding community. This study aims to assess the community's perception of air pollution in the area, identify their level of awareness of the impact of air pollution, and assess community participation in pollution control efforts. The research method used is qualitative with data collection through interviews and direct observation to residents living around Terjun landfill. The results showed that the community is aware of air pollution from landfill activities, especially the unpleasant odor that is more pronounced at night and the smoke from burning waste that disturbs respiratory health. The community also considers that this air pollution has a negative impact on their health, such as respiratory problems and decreased quality of life.